Modern technologies in manufacturing Selected. peer reviewed papers from the 12th International Conference on Modern Technologies in Manufacturing (MTeM) October 14-16, 2015, Cluj-Napoca, Romania - Balc, N. O. (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the 12th International Conference on Modern Technologies in Manufacturing (MTeM) October 14-16, 2015, Cluj-Napoca, Romania. The 59 papers are grouped as follows:Chapter 1: Processes of Metal MachiningChapter 2: Metal FormingChapter 3: Processing of Plastics and Composite MaterialsChapter 4: Additive Manufacturing and Non-traditional TechnologiesChapter 5: Computer Aided Design and ManufacturingChapter 6: Automation of Manufacturing Systems and AssemblyChapter 7: Manufacturing Engineering.